Moderasi Beragama dalam Pendidikan Agama Islam di SMK Harum Sentosa Perbaungan Perbaungan - Ahmad Darlis; Yudha Wijaya Lubis; Abdul Fajar Hasibuan; Muhammad Alwi Alamsyah; Win Ryansyah Ramadhan (Departement of Mathematics Education, 2023)
Religious moderation is understanding and being balanced between religious experience (exclusive) and respect for the religious practices of other people with different beliefs (exclusive). Balance in religious practice will keep us from extreme, revolutionary, and even fanatical attitudes in religion. Religious moderation is the key to creating tolerance and harmony. This study discusses religious moderation in Islamic Religious Education at SMK Harum Sentosa Perbaungan with qualitative research methods, namely by describing and describing the results of research using interview and observation techniques. Harum Sentosa Vocational School as a whole is dominated by how the managerial management of a teacher is in the classroom. Inserting religious moderation in PAI subjects at Harum Sentosa Vocational School can be done such as inserting understanding with mutual tolerance and caring for others related to the material being taught. At Harum Sentosa Perbaungan Vocational School, there are various ethnicities, tribes, religions and cultures, especially at Harum Sentosa Vocational School. This heterogeneity does not rule out the possibility of the potential to create friction or conflict that causes social imbalance. This is the need for the concept of religious moderation in Islamic Education to create balance and prosperity in the harmony of national and religious life.